The effect of cyclic temperatures on the growth of Fasciola hepatica and Lymnaea viatrix. - Claxton, J.R. (1999)
The experiment aimed to measure the effect of constant and variable temperatures on the growth of Lymnaea viatrix snails, on the development of a Peruvian isolate of Fasciola hepatica eggs and on the development of F. hepatica in the snails. This was carried out by cultivating infected and uninfected snails and fluke eggs in artificial, temperature controlled chambers. L. viatrix snails were found to develop at a rate dependent on environmental temperature, but developed at least as well under conditions of varying temperature as at the same mean constant temperature. F. hepatica eggs held at constant or varying temperatures, developed at a rate comparable to other reports. However, eggs developing at varying temperatures appeared to have reduced hatchability. Parasite development within the snails was slow, though within the limits calculated from the literature, and varying temperature did not appear to reduce development compared to constant temperatures.